Positive Reinforcement strategies in school environments: Impacts on student behavior (Research, Society and Development, 2025)
This article addresses the relevance of positive reinforcement in the teaching-learning process in Basic Education, with an emphasis on the development of emotional and social skills in children and adolescents. The research is part of the context of Basic Education, as defined by the Law of Guidelines and Bases of National Education (LDB), and aims to explore how pedagogical practices, especially positive reinforcement, can contribute to student motivation and engagement, favoring their retention and success in school. The methodology adopted involved a qualitative analysis of teaching strategies, based on a bibliographic review. The main results indicate that the effective use of positive reinforcement, combined with inclusive practices, benefits not only cognitive learning, but also the social integration and emotional development of students. The study highlights the importance of motivational strategies and the internalization of values in improving pedagogical practices in education, suggesting the continuation of research with this focus among basic education teachers and undergraduate students in pedagogy and psychology to promote the integral development of students through their interventions in professional practice.